Digirealty- Lodha Venture - Bhanushali, Shubham (ATLAS SkillTech University, 2024)
Throughout my internship as a Strategic Alliance & Partnership Intern at BelleVie, I immersed myself in the dynamic realm ofMumbai's home services and products industry. This experience granted me profound insights into the intricate web of challengesand opportunities that emerging companies like BelleVie must navigate. A prominent theme that emerged was the pivotal role ofstrategic alliances and partnerships in propelling business expansion. Collaborating closely with BelleVie's top-tier leadership team and their diverse range of partners, I witnessed firsthand how thesesynergistic relationships could significantly amplify a company's market presence. It became evident that crafting and nurturingsuch partnerships were foundational aspects of my internship. One overarching lesson that reverberated throughout my internship was the unwavering focus on delivering a user-centricexperience. This encompassed elements such as ensuring the website's seamless adaptability across various devices and creatinginformative and engaging content. Placing the user at the epicenter of all business decisions was not just a preference; it was astrategic necessity. Cultivating credibility in the eyes of potential customers emerged as another pivotal aspect of my internship. This was achievedthrough transparent and honest communication, the showcasing of authentic customer reviews and testimonials, and prominentlydisplaying affiliations with esteemed industry organizations and certifications. These strategies were instrumental in nurturing trustand confidence among prospective clients.
Project Report on Digirealty- Lodha Venture (2022-24) Under the Guidance of Prof. David Wittenberg
Keywords: Real Estate; Marketing